(untitled) (Doctor Virtualis, 2025)
The article examines how Hegel analyzes the Middle Ages as an historical and cultural entity. According to Hegel, history also means history of philosophy, just as philosophy is fully part of the material historical process. In both dimensions, Hegel seeks the evolution of the Spirit and the development of what he considers the telos of history: the human subject’s awareness that consciousness is constituted by freedom. Historical periods and processes of intellectual development are conceived by Hegel as unitary entities that evolve cumulatively, even if their unfolding is not linear. Hegel’s thought can be defined as structurally critical, because it treats the relationship between subject and world as always to be transcended, and reality can never be hypostatized or considered only in itself, but it must always be correlated with its own negative, with what it is not yet, in view of the full development of human faculties and the possibilities of Reason. The central question of the article is thus: how does Hegel conceptualize the Middle Ages within this theoretical structure? What place does he assign it in the history of Spirit’s evolution?